Design And Build An Educational Game Application For Learning English Based On Android - M. Agung Oki Prayugo; Rika Rosnelly; Hetty Zahrani (SISFOTENIKA, 2022)
The media of teaching English in Indonesia is currently growing rapidly, especially with teaching that is taught from an early age to 4-year-olds. Then an educational game was created for learning English based on Android which would later be effectively used as a means of student learning. Current learning, especially in the world of education, still uses face-to-face media, therefore it is still difficult for students to use English vocabulary (Vocabulary) correctly because they still use book media only, and therefore students' lack of interest in learning English. This Android-based educational game will be designed with an attractive and interactive appearance and can be used effectively and efficiently in the world of education and society today. In this study, an educational game application in English will be built which will explain some vocabulary material in the form of English and games to increase children's interest in learning